PENERAPAN TEKNOLOGI AUGMENTED REALITY PADA WEBSITE PENDAFTARAN SISWA BARU - Asmiatun, Siti; Umam, Miftachul (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2024)
This research implements Augmented Reality technology on the New Student Admission (PPDB) platform at MA Darul Falah Sirahan. Augmented Reality allows users to experience the physical environment with virtual elements, creating an interactive and immersive experience. The purpose of implementing Augmented Reality on the PPDB website is to enhance the experience for prospective students, parents, teachers, and staff by providing in-depth insights into the school and presenting information more effectively. The research involves the development of the PPDB website to facilitate online registration without physical presence. The site is integrated with AR technology, enabling users to view additional information about facilities, academic programs, and extracurricular activities by directing their mobile devices to images on the website. The MDLC method is employed, combining images, sound, video, and animations in the application/web. Laravel, Unity, and Vuforia frameworks are utilized in development. The research outcome is the development of a PPDB website integrated with Augmented Reality to enhance user engagement.